2020
DOI: 10.3390/polym12102312
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized KIT-6/Polysulfone Mixed Matrix Membranes for Enhanced CO2/CH4 Gas Separation

Abstract: The development of mixed matrix membranes (MMMs) for effective gas separation has been gaining popularity in recent years. The current study aimed at the fabrication of MMMs incorporated with various loadings (0–4 wt%) of functionalized KIT-6 (NH2KIT-6) [KIT: Korea Advanced Institute of Science and Technology] for enhanced gas permeation and separation performance. NH2KIT-6 was characterized by field emission scanning electron microscope (FESEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The produced KIT‐6 and the catalyst are uniformly mesoporous, as shown by the sample's IUPAC categorization of IV isotherm 73 . The catalyst exhibits a type IV(a) isotherm with H1 type hysteresis loop, which is characteristic of mesoporous materials even after stabilization of Cu(II)[Sal(PMeOSi)DETA] on KIT‐6 74–78 . The synthesized catalyst has a surface area of 174.14 m 2 /g, according to the BET diagram which is lower than the mesoporous surface area of KIT‐6 (581.14 m 2 /g) 72 and the pore volume of Cu(II)[Sal(PMeOSi)DETA]@KIT‐6 catalyst is equal to 0.3218 cm 3 /g, which is less than the pore volume of KIT‐6 (0.7734 cm 3 /g) 72 .…”
Section: Resultsmentioning
confidence: 98%
“…The produced KIT‐6 and the catalyst are uniformly mesoporous, as shown by the sample's IUPAC categorization of IV isotherm 73 . The catalyst exhibits a type IV(a) isotherm with H1 type hysteresis loop, which is characteristic of mesoporous materials even after stabilization of Cu(II)[Sal(PMeOSi)DETA] on KIT‐6 74–78 . The synthesized catalyst has a surface area of 174.14 m 2 /g, according to the BET diagram which is lower than the mesoporous surface area of KIT‐6 (581.14 m 2 /g) 72 and the pore volume of Cu(II)[Sal(PMeOSi)DETA]@KIT‐6 catalyst is equal to 0.3218 cm 3 /g, which is less than the pore volume of KIT‐6 (0.7734 cm 3 /g) 72 .…”
Section: Resultsmentioning
confidence: 98%
“…Mohamat et al [31] reported that the incorporation of 3wt% zeolite T in polysulfone membrane enhanced CO 2 /CH 4 selectivity from 2.63 to 3.37, with CO 2 permeability of 78.90 GPU. On the other hand, the presence of 2 wt% of KIT-6 (KIT: Korea Advanced Institute of Science and Technology), a silica mesoporous, could improve CO 2 /CH 4 selectivity to 32.4, with CO 2 permeability of 5.4 Barrer [32]. However, the disadvantage of MMM is the weak interaction between the polymer matrix and the filler, which can form voids [33] and thereby reduce the separation performance.…”
Section: Introductionmentioning
confidence: 99%
“…These systems can be potentially used to address the problems of permeability and selectivity tradeoff. It is composed of a solid phase dispersed in a polymer [1]. The high selectivity of the solid filler, attributable to the increase in the number of voids, promotes the permeation of small molecules and improves the permeant sorption selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a combination of diffusion and sorption selectivities has been used to fabricate MMMs. Amine-functionalized mesoporous silica that can be used as fillers in MMMs to achieve CO 2 separation has gained importance [1]. Different fillers, such as zeolites and silica, have been investigated [2].…”
Section: Introductionmentioning
confidence: 99%